Comparative Analysis of Results of Online and Offline Customer Satisfaction & Loyalty Surveys in Banking Services in Montenegro - Milorad Jovović; Bojana Femić-Radosavović; Milena Lipovina-Božović (Journal of Central Banking Theory and Practice, 2017)
The logic that customer satisfaction is the starting point of marketing and business activities is based on the assumption that customer satisfaction leads to customer loyalty, keeping in mind all of the positive effects that customer loyalty has on business success of an organization. Because of this, marketing and management theory and practice dedicate particular attention to the concepts of customer satisfaction and loyalty. In this paper we will use the surveys of customers of banking services not only to show the levels of their satisfaction and loyalty, but also to make a comparative analysis of data obtained through online and offline research. This approach was made possible because the research was carried out on a sample which was divided in two groups. All of the participants answered the questions from a unique questionnaire, however, one group took the survey via the Internet (online) while data from the other group of participants was collected in the field by using printed questionnaires (offline). The findings of the comparative analysis of online and offline survey results are presented in the final part of the paper.
Keywords: M39; G20; 330; Customer satisfaction; loyalty; services; banking; online vs offline research